National Rural Manpower Conference Summary of Proceedings (Atlanta, Georgia, January 18-20, 1971). - Manpower Administration (DOL), Washington, DC. U.S. Training and Employment Service; Manpower Administration (DOL), Washington, DC. U.S. Training and Employment Service ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
An annual event since 1951, this conference was held to: (1) review the previous year's activities of the Rural Manpower Service and its cooperating agencies; (2) discuss plans for the new year; and (3) study the problems of rural areas. Most of the 250 persons attending the 3-day conference were officials of the Manpower Administration and its affiliated State agencies. The speeches, workshops, and special meetings revealed "a definite break with the past". The new strategy of the Rural Manpower Service placed less emphasis on farm placement activity and more on experimentation to find new ways of helping rural workers--both farm and nonfarm. This report gives the speeches and the discussions from the plenary sessions, workshops, and special meetings. Topics covered include: rural manpower strategy; the manpower challenge in rural areas; the commitment to serve rural America; artificial barriers to employment--recognizing cultural differences; agricultural unionization; new approaches for organizing the delivery of manpower services; rural manpower staff development; promotion of involvement and interagency coordination; the Migrant Experimental and Demonstration Project; and Florida and Texas recruitment. (NQ)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Agency Role; Conference Reports; Coordination; Delivery Systems; Employment Patterns; Labor Force Development; Migrant Workers; Program Descriptions; Rural Areas; Speeches; State Agencies; Workshops; Collected Works, Proceedings